Islamski Front Wyzwolenia Moro i Abu Sajjaf. Ewolucja islamskiej aktywności terrorystycznej na Filipinach - Wejkszner, Artur (Przegląd Strategiczny, 2011)
The main aim of this article is to show the evolution of Islamic terrorism in the Philippines. This country has been plagued by insurgencies throughout the history. The Muslim secessionist movement in the Southern Philippines is rooted in the centuries-old resistance of Muslim Filipinos against Spanish colonization. The destruction of the traditional patterns of authority, destruction of communal autonomy and the introduction of a new religion fueled the resistance of the Muslims in Mindanao. The Muslim secessionist movement is comprised at the onset of the XXI century of two main groups: The Moro Islamic Liberation Front (MILF) and the Abu Sayyaf Group. These groups with links to Al Qaeda have established the Islamic foothold in the Southern Philippines in past two decades. The Moro Islamist Liberation Front (MILF) have been the vanguard of the Islamic movement in the Bangsamoro homeland in Mindanao and the neighbouring islands. The MILF was officially formed in 1984. Its founder, Hashim Salamat, supported by ethnic Maguindanaos from Mindanao, split few years earlier from the Moro National Liberation Front (MNLF). In January 1987, the MNLF signed an agreement relinquishing its goal of independence for Muslim regions and accepting the government’s offer of autonomy. The Moro Islamic Liberation Front refused to accept the accord. MILF has been non active as a terrorist organization since 2003. Abu Sayyaf was founded by a Philippine veteran of Afghan-SovietWar. It has gone through several iterations since its emergence in 1991. It devolved from an Islamist militant organization bent on creating a separate Muslim state in the southern Philippines to a loose collection of kidnap-for-ransom gangs after the 1998 death of founder Abdurajak Abubakar Janjalani. Now a much leaner group than it was Abu Sayyaf continues to exist as several different factions.